Determinants Quality of Life For Chronic Kidney Disease Patients Undergoing Hemodialysis Therapy - Nurarifah; Gustini; Sukmawati; Estelle Lilian Mua; Alfrida Semuel Ra’bung (Public Health of Indonesia)
Background:Hemodialysis is a kidney replacement therapy for patients with chronic kidney disease (CKD) aimed at removing excess fluid and waste products from the bloodstream and extending life expectancy. Although hemodialysis is considered the most effective therapy for increasing the life expectancy of CKD patients, it is associated with several side effects that can impact patients' overall well-being.